1998
DOI: 10.1021/jm970239z
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Pharmacophore Model for Anandamide Using Constrained Conformational Searching and Comparative Molecular Field Analysis

Abstract: Constrained molecular dynamics simulations on anandamide, together with a systematic distance comparison search, have revealed a specific low-energy conformer whose spatial disposition of the pharmacophoric elements closely matches that of HHC. This conformer enables near superposition of the following: (1) the oxygen of the carboxyamide and the phenolic hydroxyl group of HHC, (2) the hydroxyl group of the ethanol and the cyclohexyl hydroxyl group of HHC, (3) the alkyl tail and the lipophilic side chain of HHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 32 publications
3
75
0
Order By: Relevance
“…A similar low energy helical conformation of anandamide has been reported previously using computational methods (36). As shown previously, the cannabinoid CB 1 receptor recognizes NAEs with fatty acid chains having at least (i) three homoallylic double bonds and (ii) five terminal unsaturated carbons (25).…”
Section: Discussionsupporting
confidence: 83%
“…A similar low energy helical conformation of anandamide has been reported previously using computational methods (36). As shown previously, the cannabinoid CB 1 receptor recognizes NAEs with fatty acid chains having at least (i) three homoallylic double bonds and (ii) five terminal unsaturated carbons (25).…”
Section: Discussionsupporting
confidence: 83%
“…To investigate whether the introduction of the 1-hydroxy-2E,4Z-pentadiene system in AEA influenced the orientation and distances of pharmacophoric groups in the HAEAs, the pharmacophores of the reference compound CP-55,940 were compared with pharmacophores in the (H)AEA series ( Figure 5). The pharmacophoric groups were identified based on the model of Tong et al 25 This model was capable of discriminating between structurally related compounds exhibiting different pharmacological potencies for the CB 1 receptor, i.e., AEA and prostaglandinethanolamide. Furthermore, it could be used in a three-dimensional quantitative structure-activity relationship (3D QSAR) study to predict the K i value of AEA.…”
Section: Conformational Analysis Of (H)aeasmentioning
confidence: 99%
“…Furthermore, the cyclohexyl OH in the cannabinoids and the corresponding terminal OH of AEA both enhance binding, but their absence (as in THC and alkyl arachidonate derivatives) does not eliminate activity. 25 First, the conformation of CP-55,940 was analyzed to find the orientation of the hexyl ring in relation to the phenyl ring, and the orientation of the alkyl side chain. NOESY data for CP-47,497 (in chloroform) have shown that the orientation of the two rings around the C 6 -C 7 bond, determined by the dihedral angle C 5 -C 6 -C 7 -C 8 (see Figure 5 for numbering), is -60°rather than 120°.…”
Section: Conformational Analysis Of (H)aeasmentioning
confidence: 99%
See 2 more Smart Citations